Northeast Asia Nuclear-Weapon-Free Zone - Necessity and Challenges - Kawasaki, Akira (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i14.28 Mongolian Journal of International Affairs No.14 2007 pp.88-95